Exploring the Dualities of ODL Experienced by the Employed University Level Students in Nepal - Bohara, Lal Bahadur (Journal of Jayaprithvi Multiple Campus, 2025)
This study purposes to explore the opportunities and challenges of ODL experienced by the employed university level students in Nepal with respect to the socio-cultural context. Moreover, it delved to shed light on their strategic dynamics to workout both the work (earning) and study (learning) at a time. For the study, I attempted to use the narrative inquiry as the research design and the purposive information were collected with the help of the in-depth interview and virtual Focused Group Discussion (FGD) comprehensively. Similarly, for this, I had selected both the rural and urban parts of Nepal as the research site and the Five employed university level students studying in ODL mode were selected as the participants purposively. From the study, it was explored that the employed ODL students were under pressures of work and study and the unnecessary social stigmas in the community level with respect to the socio-physical gaps among themselves. However, such misunderstandings got reformed after the encroachment of Covid-19 along with the use of the ODL and net/internet mediated instruction everywhere. Next, the context of ODL appeared more favorable and friendly to those with the extrovert and open personalities than the introvert and close ones concerning the way of course conduction. Conversely, with some shortcomings of the ODL, the employed university level students were able to pursue their work and study together. I think this study would be purposeful to anyone who wants to be familiar with the dualities of ODL in Nepal and outsides and the respective stakeholders could be benefitted to have been reforming the possible drawbacks and welcoming the favorable situation as soon as possible. In conclusion, it overviewed the dualities of ODL in Nepal.